2011
DOI: 10.1124/jpet.111.180240
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo P-Glycoprotein Transport Characteristics of Rivaroxaban

Abstract: Rivaroxaban, an oral, direct factor Xa inhibitor, has a dual mode of elimination in humans, with two-thirds metabolized by the liver and one-third renally excreted unchanged. P-glycoprotein (P-gp) is known to be involved in the absorption, distribution, and excretion of drugs. To investigate whether rivaroxaban is a substrate of P-gp, the bidirectional flux of rivaroxaban across Caco-2, wild-type, and P-gp-overexpressing LLC-PK1 cells was investigated. Furthermore, the inhibitory effect of rivaroxaban toward P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
154
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(167 citation statements)
references
References 32 publications
9
154
0
4
Order By: Relevance
“…Of further note, previous studies indicated that rivaroxaban is a shared substrate of the drug transport proteins MDR1 and BCRP, whereas anticoagulant vitamin K antagonists are no strong substrates of MDR1 [17][18][19]. MDR1 inhibitors and loss-of-function BCRP polymorphisms may therefore alter rivaroxaban pharmacokinetics, and further studies may explore the potential role of these factors for rivaroxaban-induced DILI.…”
Section: Discussionmentioning
confidence: 97%
“…Of further note, previous studies indicated that rivaroxaban is a shared substrate of the drug transport proteins MDR1 and BCRP, whereas anticoagulant vitamin K antagonists are no strong substrates of MDR1 [17][18][19]. MDR1 inhibitors and loss-of-function BCRP polymorphisms may therefore alter rivaroxaban pharmacokinetics, and further studies may explore the potential role of these factors for rivaroxaban-induced DILI.…”
Section: Discussionmentioning
confidence: 97%
“…P-gp was assumed to be solely responsible for the net renal secretion of rivaroxaban. A reversible K i value derived from a study using a known P-gp substrate digoxin was used for erythromycin, despite a recent report of minimal impact on P-gp mediated rivaroxaban transport in vitro by erythromycin [10]. Further model verification is needed for erythromycin's inhibition mechanisms, including sensitivity/uncertainty analyses of inhibition parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, passive glomerular filtration and active secretion mediated by transporters (likely P-glycoprotein, P-gp and/or breast cancer resistance protein, [1,5,9]) contribute to rivaroxaban renal clearance (CL R ) at a ratio of 1:5 [1,5]. The clearance of rivaroxaban appears to decrease in the elderly [1, 5,10].…”
Section: Introductionmentioning
confidence: 99%
“…Drugs that exhibit strong effects on these proteins therefore have the potential to influence the pharmacokinetics, and thus the safety and efficacy profile, of rivaroxaban 7, 8. Consequently, strong inhibitors of both CYP3A4 and P‐gp are not recommended for systemic concomitant use with rivaroxaban 9.…”
Section: Introductionmentioning
confidence: 99%